Pengaruh Latihan Circuit Training Terhadap Kebugaran Jasmani Siswa SMP Negeri 2 Mataram - Adlan Ali Sukron; Ahmad Firjatulloh (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to determine the effect of Circuit Training on the physical fitness of students at SMP Negeri 2 Mataram. The background of this research is based on the importance of improving physical fitness during adolescence, especially in the school environment, as a foundation for health and academic achievement. The method used in this study is an experimental method with a one-group pretest-posttest design. The research subjects consisted of 30 eighth-grade students selected through purposive sampling. The instrument used to measure physical fitness was the Indonesian Physical Fitness Test (TKJI) for ages 13–15. The Circuit Training program was implemented over six weeks with a frequency of three sessions per week, consisting of various types of exercises such as sprinting, jump rope, push-ups, sit-ups, and shuttle runs. Data analysis using a paired sample t-test showed a significant improvement in students’ physical fitness after participating in the training program (p < 0.05). The average physical fitness score of the students increased significantly from pretest to posttest. These findings indicate that Circuit Training is effective as a method to improve the physical fitness of junior high school students. It can be concluded that a structured and consistent implementation of Circuit Training can have a positive impact on students’ physical fitness. Therefore, it is recommended that physical education teachers integrate this training into school sports learning activities.